2022
DOI: 10.1186/s12933-022-01551-3
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of cardiometabolic risk factors in Chinese population: a narrative review

Abstract: With rapid economic growth and changes at all levels (including environmental, social, individual), China is facing a cardiovascular disease (CVD) crisis. In China, more than 40% of deaths are attributable to CVDs, and the number of CVD deaths has almost doubled in the past decades, in contrast to a decline in high-income countries. The increasing prevalence of cardiometabolic risk factors underlies the rise of CVDs, and thus curbing the rising cardiometabolic pandemic is imperative. Few articles have addresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…Although superior optimized strategies for revascularization and medication treatment have been developed and applied recently, there is still a high incidence of recurrent cardiovascular events [3,4]. Therefore, it is of great clinical importance to improve the risk stratification to facilitate the management of patients with CAD, which is also a great challenge [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although superior optimized strategies for revascularization and medication treatment have been developed and applied recently, there is still a high incidence of recurrent cardiovascular events [3,4]. Therefore, it is of great clinical importance to improve the risk stratification to facilitate the management of patients with CAD, which is also a great challenge [5].…”
Section: Introductionmentioning
confidence: 99%
“…Only when MVPA is higher than 77.1 min/day, increasing the MVPA duration can obtain a higher LDL-C improvement effect. In clinical practice, WC is the evaluation indicator of abdominal obesity, SBP and DBP are the evaluation indicators of hypertension, and blood lipid level is used to judge whether dyslipidemia occurs, in addition, FPG, FINS and HOMA-IR are indicators of glucose metabolism ( Li et al, 2022 ). All of these cardiometabolic risk indicators were associated with an increased risk of cardiovascular disease (CVD) ( Park and Choi, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have important public health implications. China is experiencing an epidemic of obesity and metabolic diseases due to rapid economic development and lifestyle changes [28]. For example, an epidemiologic study indicated that the prevalence of abdominal obesity increased greatly among Chinese adults (especially those aged 40-80) from 1993 to 2015 [29].…”
Section: Discussionmentioning
confidence: 99%